Prediksi perilaku korupsi dalam perspektif dimensi budaya model Hofstede - Eben Ezer Nainggolan (INNER: Journal of Psychological Research, 2022)
Abstract Corruption is a global phenomenon. No country in the world is free from corruption issues, even Denmark and Newzeland which are ranked one and two cleanest countries respectively, still have index scores of 88 and 87 (not yet reached 100). This literature study aims to find answers to the question of how to predict corrupt behaviour from the perspective of the cultural dimensions of Hofstede's model. This research design is review research. Researchers searched the literature related to problem-solving skills through Google Scholar. The hermeneutic technique is used to analyze the literature that is in accordance with the research objectives. The results showed that the Power Distance Dimension and the Individualism-Collectivism Dimension had a strong indication of having a relationship with the Corruption Perception Index. Keywords: Corruption Behavior, Cultural Perspective, Hofstede's Model